Measuring SMEs’ Sustainability: A Literature Review and Agenda for Research - Prabawani, Bulan (International Journal of Management and Sustainability, 2013)
Environmental hazards can be caused by firms’ lack of awareness of social and natural concerns. Firms of all sizes can have significant environmental impacts at regional and global levels. Small and medium-sized enterprises (SMEs) form the majority of all businesses in developing and developed economies, contribute to national GDP and make significant distributions to employment, but they have fundamental problems in terms of resources and this tends to harm their business sustainability. Various methods to review business sustainability have been developed. However, researchers have not yet assessed SMEs’ sustainability levels using comprehensive measures. This is particularly problematic in the manufacturing sector because the purpose of this review of SMEs’ sustainability is the criteria that can be used to assess SMEs’ sustainability levels. These criteria include firms’ internal and external factors and stakeholders as well as present and future interests. As such this paper establishes a basis for future research.